Seismotectonic Analysis and Seismic Potensial of The Sumatra Region Using The Guttenberg-Richter Method - Yusrila, Yoga; Syafriani, Syafriani; Hamdi, Hamdi; Dwiridal, Letmi (Department of Physics, Universitas Negeri Padang, 2024)
Sumatera is one of the most seismically active regions in Indonesia. This is due to the presence of subduction zones and active faults that influence the plate tectonic activity of the region, resulting in many earthquake events that cause damage and loss. One of the efforts to mitigate earthquake disasters is the analysis of seismotectonic parameters, which are indicated by the a-value and b-value of the Gutenberg-Richter equation in the earthquake frequency-magnitude relationship. Low seismotectonic parameters (a-value) and (b-value) can be interpreted as low seismic activity and high local rock stress conditions, and vice versa high (a-value) and (b- value). In this study, the analysis was performed spatially and temporally from the National Earthquake Information Center United States Geological Survey (NEISUSGS) earthquake catalogue. The data obtained in the form of longitude, latitude, depth, magnitude, time and location of the earthquake event, the data are limited to M ≥ 4.0Mw and Depth ≤ 350KM in the Sumatera region with the boundaries of 6030'LU-6°30'LS and 94BT-106°BT for the period 1990-2022. Based on the estimation results of the Guttenberg-Richter method in ZMAP v6 software, the b-value is 0.92-1.04 and the a-value is 7.42-7.97, with a return period of 6.5 Mw earthquakes generally ranging from 5-25 years.